Investigation of effect of the number of ground control points and distribution on adjustment at WorldView-2 Stereo images - Omer MUTLUOGLU; Murat YAKAR; Haci Murat YİLMAZ (International Journal of Applied Methods in Electronics and Computers, 2015)
Nowadays, Very High Resolution Satellite (VHRS) images have been used for many applications intensively. Using of the digital satellite images in relevant approaches may give more accurate ideas about the researched fields. Besides, different methods could be used for production of maps from relevant digital data in many scientific disciplines. One of these methods is to use VHRS images. The most importance reason of using the maps, which are derived from VHRS images, is accuracy of data. To obtain maps from VHRS images or use VHRS images as map, the VHRS images required rectification. For a accurate rectification process, Ground Control Points (GCPs) must be marked in the field. In this study the effect of number of GCP and distrubition on the surface has been investigated on stereo WorldView-2 (WV-2) at rectification of VHRS images. The effect of distribution of control points at the terrain has seen to be more effective than the effect of number of control points upon the adjustment results.